2015
DOI: 10.1007/978-3-319-21401-6_41
|View full text |Cite
|
Sign up to set email alerts
|

MathCheck: A Math Assistant via a Combination of Computer Algebra Systems and SAT Solvers

Abstract: We present a method and an associated system, called Math-Check, that embeds the functionality of a computer algebra system (CAS) within the inner loop of a conflict-driven clause-learning SAT solver. SAT+CAS systems, a la MathCheck, can be used as an assistant by mathematicians to either counterexample or finitely verify open universal conjectures on any mathematical topic (e.g., graph and number theory, algebra, geometry, etc.) supported by the underlying CAS system. Such a SAT+CAS system combines the effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
(35 reference statements)
1
17
0
Order By: Relevance
“…The Ruskey-Savage conjecture (that every matching of a hypercube can be extended into a Hamiltonian cycle) was previously known to hold in the orders n = 2, 3, and 4 [29]. Using MathCheck we showed that the conjecture also holds in the order n = 5 for the first time [79].…”
Section: The Sat+cas Paradigmmentioning
confidence: 84%
See 1 more Smart Citation
“…The Ruskey-Savage conjecture (that every matching of a hypercube can be extended into a Hamiltonian cycle) was previously known to hold in the orders n = 2, 3, and 4 [29]. Using MathCheck we showed that the conjecture also holds in the order n = 5 for the first time [79].…”
Section: The Sat+cas Paradigmmentioning
confidence: 84%
“…1. The Ruskey-Savage conjecture (see [78,79]). This conjecture states that any matching of a hypercube graph can be extended to a Hamiltonian cycle.…”
mentioning
confidence: 99%
“…The fact that satisfiability checking and symbolic computation had great potential synergy was first pointed out by Erika Ábrahám in an invited talk at the conference ISSAC in 2015 (Ábrahám 2015). At almost the same time this synergy was demonstrated by the system MATHCHECK presented at the conference CADE (Zulkoski, Ganesh, and Czarnecki 2015). The system MATHCHECK coupled a SAT solver with a computer algebra system and solved open cases of two conjectures in graph theory and was later extended to solve open cases in combinatorial conjectures (Zulkoski et al 2017).…”
Section: The Sat+cas Paradigmmentioning
confidence: 97%
“…The idea of combining SAT solvers with computer algebra systems originated independently in two works published in 2015: In a paper at the conference CADE entitled "MATHCHECK: A Math Assistant via a Combination of Computer Algebra Systems and SAT Solvers" by Zulkoski et al (2015) and in an invited talk at the conference ISSAC entitled "Building Bridges between Symbolic Computation and Satisfiability Checking" by Ábrahám (2015). The paradigm was also anticipated by Jovanović and de Moura (2012) who used CAS techniques in SAT-like search algorithms.…”
Section: The Sat+cas Paradigmmentioning
confidence: 99%
“…Secondly, similar in style to (Zulkoski et al, 2015) we incorporate functionality from computer algebra systems to increase the efficiency of the search in what we call the "SAT+CAS" paradigm. This approach of combining computer algebra systems with SAT or SMT solvers was also independently proposed at the conference ISSAC by Ábrahám (2015).…”
Section: Introductionmentioning
confidence: 99%